Tension-induced twist of twist-spun carbon nanotube yarns and its effect on their torsional behavior - Jeon, Seung-Yeol; Kwon, Dongil; Yu, Woong-Ryeol (NATURE PUBLISHING GROUP, 2018)
Twist-spun carbon nanotube (CNT) yarns exhibit a large and reversible rotational behavior under specific boundary conditions. In situ polarized Raman spectroscopy revealed that a tension-induced twist provides reversibility to this rotation. The orientation changes of individual CNTs were followed when twist-spun CNT yarns were untwisted and subsequently retwisted. Twist-spun CNT yarn, when untwisted and subsequently retwisted under the one-ended tethered boundary condition, showed irreversible orientation changes of the individual CNTs due to snarls formed during the untwisting operation, which resulted in macroscopic irreversible rotational behavior of the CNT yarns. In contrast, the orientation changes of the individual CNTs in twist-spun CNT yarn, when operated under the two-ended tethered boundary condition, were hysteretically reversible due to a tension-induced twist, which has not been reported previously. Indeed, the tension-induced twist was observed by following the orientation change of individual CNTs in elongated CNT yarns, which simulated the deformational behavior of the CNT yarn rotated under the two-ended tethered boundary condition.